Intraspecific Trait Variability in Andropogon gerardii, a Dominant Grass Species in the US Great Plains - Bachle, Seton; Griffith, Daniel M.; Nippert, Jesse B. (Frontiers in Ecology and Evolution, 2018)
The climatic conditions in the North American Great Plains are highly variable, characteristic of an inter-continental climate. Antecedent climate history has impacted the flora of Great Plains grasslands, resulting in high species richness as well as dominance by only a few grass species, such as Andropogon gerardii. While the productivity of A. gerardii is well described, the individual physiological and morphological characteristics that confer species dominance over wide spatial gradients are not clearly understood. We performed a literature search to assess intra-specific trait variability of A. gerardii from as many locations as possible. Ultimately, only 13 locations in the Great Plains have reported common plant functional traits (PFTs) for this species. To best represent site-specific climate conditions, plant functional trait data (8 PFTs) were collected from literature reporting ambient growing conditions, and excluded experimental manipulations. For most PFTs, we found insufficient data to fully quantify the range of variation across the geographical extent of A. gerardii dominance. This is surprising given that we focused on the most abundant grass in one of the most well-studied regions globally. Furthermore, trait data collected from our literature search showed a high degree of variability, but no strong relationships were observed between mean trait values and climate predictors. Our review of the literature on A. gerardii suggests a role for trait variability as a mechanism enabling the dominance of this species across large regions such as the Great Plains of North America.